1977
DOI: 10.1137/1019005
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-Newton Methods, Motivation and Theory

Abstract: This paper is an attempt to motivate and justify quasi-Newton methods as useful modifications of Newton's method for general and gradient nonlinear systems of equations. References are given to ample numerical justification; here we give an overview of many of the important theoretical results and each is accompanied by sufficient discussion to make the results and henc6 the methods plausible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
533
0
20

Year Published

1978
1978
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,325 publications
(557 citation statements)
references
References 41 publications
4
533
0
20
Order By: Relevance
“…Dennis and Moré [15] showed that the Broyden update can also be obtained by minimizing E(J k+1 ) = J k+1 − J k 2 F with respect to terms of J k+1 , subject to the secant condition (4).…”
Section: Broyden's Methodsmentioning
confidence: 99%
“…Dennis and Moré [15] showed that the Broyden update can also be obtained by minimizing E(J k+1 ) = J k+1 − J k 2 F with respect to terms of J k+1 , subject to the secant condition (4).…”
Section: Broyden's Methodsmentioning
confidence: 99%
“…The Jacobian is Equations (A.14) and (A.15) can be obtained using Sherman and Morrison's lemma [20]. Note that these equations only involve matrix products.…”
Section: A1 Consistent Tangent Moduli For Substepping With the Forwamentioning
confidence: 99%
“…Consideration of these algorithms led to the research on so-called quasi-Newton methods, surveyed in [2,3]. Potra-Ptk [17,18,19] used nondiscrete induction to obtain convergence and error bounds for the Newton, multistep Newton, and generalized regular falsi methods.…”
Section: Moreover If G(t)mentioning
confidence: 99%